2015
DOI: 10.1063/1.4922525
|View full text |Cite
|
Sign up to set email alerts
|

Phase imaging microscopy for the diagnostics of plasma-cell interaction

Abstract: Single beam Fourier transform digital holographic quantitative phase microscopy Appl. Phys. Lett.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Another important reason for the stronger anti-tumor effect of direct CAP treatment could be physical. Next to RONS production, CAP also generates thermal-and ultraviolet (UV) radiation, which also have a strong impact on tumor cell behavior [54][55][56], and which are not available in the case of indirect treatment with PTS.…”
Section: Discussionmentioning
confidence: 99%
“…Another important reason for the stronger anti-tumor effect of direct CAP treatment could be physical. Next to RONS production, CAP also generates thermal-and ultraviolet (UV) radiation, which also have a strong impact on tumor cell behavior [54][55][56], and which are not available in the case of indirect treatment with PTS.…”
Section: Discussionmentioning
confidence: 99%
“…263 "Real-time" QPI measurements of blood samples have been demonstrated, utilizing parallel computing strategies to calculate diagnostically relevant cell parameters without storing phase images, allowing for smaller electronic storage and data transmission requirements, which could benefit remote diagnoses of RBC diseases. 264 QPI has also been used to measure morphology changes in HTori thyroid cells during treatment with plasma from a nanosecond dielectric barrier discharge, 265 changes in macrophages from chemically induced apoptosis and dynamic phagocytosis, 201 and for sperm selection for bovine in vitro fertilization. 266 SLIM and tissue spatial correlation analysis was used to assess breast cancer fixed tissue microarrays and showed a 94% sensitivity and 85% specificity for cancer detection 267 (Figure 5d), independent of tissue staining quality.…”
Section: Qpi Applications In Screening and Drug Sensitivity Measurementmentioning
confidence: 99%
“…In 2015, Ohene et al observed the benefit of the high contrast of CGM to monitor the deformation and condensation of living cells during apoptosis . The study mainly benefited from the good contrast of CGM, not from the quantitative nature of the measurements.…”
Section: Historical Review Of the Applicationsmentioning
confidence: 99%